2015
DOI: 10.1111/evo.12823
|View full text |Cite
|
Sign up to set email alerts
|

The causes of selection on flowering time through male fitness in a hermaphroditic annual plant

Abstract: Flowering is a key life-history event whose timing almost certainly affects both male and female fitness, but tests of selection on flowering time through male fitness are few. Such selection may arise from direct effects of flowering time, and indirect effects through covariance between flowering time and the environment experienced during reproduction. To isolate these intrinsically correlated associations, we staggered planting dates of Brassica rapa families with known flowering times, creating populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 82 publications
(154 reference statements)
0
26
0
Order By: Relevance
“…Our detection of VAfalse(Wfalse) and G × E for fitness illustrates the power of our experimental quantitative genetic approach coupled with aster analysis. Direct measures of the process of genetic selection are not often undertaken (Austen and Weis ). In contrast with our finding of substantial VAfalse(Wfalse) in two sites, a study of a natural population of the collared flycatcher suggested a negative relationship between the heritability of morphological traits and their association with lifetime reproductive success, and found a heritability of 0 in lifetime reproductive success (Gustafsson ).…”
Section: Discussionmentioning
confidence: 99%
“…Our detection of VAfalse(Wfalse) and G × E for fitness illustrates the power of our experimental quantitative genetic approach coupled with aster analysis. Direct measures of the process of genetic selection are not often undertaken (Austen and Weis ). In contrast with our finding of substantial VAfalse(Wfalse) in two sites, a study of a natural population of the collared flycatcher suggested a negative relationship between the heritability of morphological traits and their association with lifetime reproductive success, and found a heritability of 0 in lifetime reproductive success (Gustafsson ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong selection for young AAF when AAF and JDF were uncorrelated rejected this hypothesis [8]. By comparing results of the genetic and mating opportunities methods, we further excluded mating opportunity as the primary driver of selection on AAF.…”
Section: (C) Flowering Time Evolution Through Male Fitnessmentioning
confidence: 99%
“…We have previously speculated that the unknown factor driving selection for young AAF in the uncorrelated population could be negative covariance between AAF and pollen quality [8]. Such covariance would be masked in the positive and negative populations, because these two treatments affected the date on which pollen of a given AAF was dispersed and deposited on stigmas, but not the identity of competitors: young-AAF pollen competed primarily with young, and old with old [24].…”
Section: (C) Flowering Time Evolution Through Male Fitnessmentioning
confidence: 99%
“…Both germination and flowering time can experience strong selection within generations to align life history events most favorably with the environment (Kalisz, 1986;VanDijk et al, 1997;Shitaka & Hirose, 1998;Donohue et al, 2000Donohue et al, , 2005aPilson, 2000;Hall & Willis, 2006;Franks et al, 2007;Sandring & Agren, 2009;Munguia-Rosas et al, 2011;Anderson et al, 2012;Colautti & Barrett, 2013;Fournier-Level et al, 2013;Akiyama & Agren, 2014;Austen & Weis, 2016;Postma & Agren, 2016;Colautti et al, 2017), and withingeneration selection on the timing of a life history event may depend upon the timing of earlier events (Forrest & Miller-Rushing, 2010;Mojica & Kelly, 2010;Donohue, 2014;Ehrlen, 2015). For example, there is pervasive evidence of selection for earlier flowering in many species, even when controlling for climate change (Munguia-Rosas et al, 2011;Austen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%